The co‐occurrence of antibiotic resistance genes between dogs and their owners in families. Issue 2 (4th May 2022) - Zhao, Ruonan; Hao, Jie; Yang, Jintao; Tong, Cuihong; Xie, Longfei; Xiao, Danyu; Zeng, Zhenling; Xiong, Wenguang
Abstract: The intimate relationship between humans and companion animals causes a unique and critical aspect of antimicrobial resistance in humans. However, a comprehensive analysis of antimicrobial resistance between companion animals and their owners is lacking. Here, we chose 13 owned dogs and 16 owners as well as 22 kennel dogs to analyze the effect of an intimate relationship between owned dogs and owners on their gut microbiome, antibiotic resistance genes (ARGs), and mobile genetic elements (MGEs) and study the correlation of antimicrobial resistance between dogs and their owners in families by metagenomics. Dog gut microbiota had a higher abundance and diversity of ARGs while owners had a higher diversity of taxonomy. In the owned dog gut microbial community, ARG and MGE compositions were significantly more similar to the owner's gut microbiota than those of others. From the perspective of families, there was a strong correlation between macrolide resistance genes between dogs and their owners. In conclusion, our study demonstrated the correlation of ARGs between dogs and their owners at a community‐wide level. These findings can alarm the use of antibiotics in companion animals, which implies the potential to harbor antimicrobial resistance and threaten public health. Abstract : The higher abundance of Gammaproteobacteria contributed to a higher resistance load in dogs. The intimate relationship affected the intestinal microbial community of dogs and their owners. The shared bacterial community caused the co‐occurrence of antibiotic resistance genes in families. Highlights: The higher abundance of Gammaproteobacteria contributed to a higher resistance load in dogs. The intimate relationship affected the intestinal microbial community of dogs and their owners. The shared bacterial community caused the co‐occurrence of antibiotic resistance genes in families.